Adaptive differentiation of murine lymphocytes. II. The thymic microenvironment does not restrict the cooperative partner cell preference of helper T cells differentiating in F1 leads to F1 thymic chimeras (The Rockefeller University Press, 1979)
The cooperating preference of helper T cells originating from F1 bone marrow, but differentiating in adult thymectomized, lethally irradiated F1 recipients reconstituted with either f1 or homozygous parental thymus grafts was investigated. Cooperating preference was assayed by determining the levels of helper activity provided by antigen-primed T cells derived from such thymic chimeras for hapten-primed B lymphocytes obtained from conventional F1 or parental donors in adoptive secondary antibody responses in vivo. The results of these analyses revealed a tendency of helper T cells derived from parental thymic chimeras to provide better help for B cells of the same parental type corresponding to the origin of the thymus graft than for the opposite parent. Such preference was, however, only marginal and rarely were differences in levels of helper activity provided to the respective parental types statistically significant. Moreover, this marginal preference, when observed, pertained only to responses of the IgG class; no concordant preference in providing helper activity for IgE antibody responses was observed even with the same populations of thymic chimera helper T cells. Finally, in no instance was there any evidence of restriction in the classical sense of presence versus absence of help as we have routinely observed in all of our previous studies concerning genetic restrictions of T-B-cell cooperative interactions. Although the basis for differences in the studies reported here when compared to observations made in cytotoxic T-lymphocyte systems is unclear, and could reflect genuine mechanistic requirements concerning what directs H-2 restrictions in helper T cells and cytotoxic T lymphocytes, respectively, it is also possible that we are placing too much faith in our interpretations of data obtained in bone marrow chimera systems than is perhaps justified by the potentially great fragility of such systems.